Shakespeare in Hawai‘i: Puritans, Missionaries, and Language Trouble in James Grant Benton’s "Twelf Nite O Wateva!", a Hawaiian Pidgin Translation of "Twelfth Night" - Hokama, Rhema (Multicultural Shakespeare: Translation, Appropriation and Performance, 2018)
In 1974, the Honolulu-based director James Grant Benton wrote and staged Twelf Nite O Wateva!, a Hawaiian pidgin translation of Shakespeare’s Twelfth Night. In Benton’s translation, Malolio (Malvolio) strives to overcome his reliance on pidgin English in his efforts to ascend the Islands’ class hierarchy. In doing so, Malolio alters his native pidgin in order to sound more haole (white). Using historical models of Protestant identity and Shakespeare’s original text, Benton explores the relationship between pidgin language and social privilege in contemporary Hawai‘i. In the first part of this essay, I argue that Benton characterizes Malolio’s social aspirations against two historical moments of religious conflict and struggle: post-Reformation England and post-contact Hawai‘i. In particular, I show that Benton aligns historical caricatures of early modern puritans with cultural views of Protestant missionaries from New England who arrived in Hawai‘i beginning in the 1820s. In the essay’s second part, I demonstrate that Benton crafts Malolio’s pretentious pidgin by modeling it on Shakespeare’s own language. During his most ostentatious outbursts, Malolio’s lines consist of phrases extracted nearly verbatim from Shakespeare’s original play. In Twelf Nite, Shakespeare’s language becomes a model for speech that is inauthentic, affected, and above all, haole.